GRIFFO PERANAN MOTIVASI ORANG TUA TERHADAP KELANJUTAN STUDI SISWA SMK NEGERI 3 TONDANO: THE ROLE OF PARENTS' MOTIVATION ON CONTINUING STUDY OF STUDENTS OF STATE VOCATIONAL SCHOOL 3 TONDANO - GRIFFO SONGGIGILAN GRIFFO; Djubir Efendy Kembuan; Tendly Maki (Pendidikan Teknik Mesin, 2022)
THe purpose of this study using the method used is the method of description, which aims to explain the relationship between the role of motivation given by parents with the continuation of children's studies. This approach is based on a theoretical framework, the ideas of experts, as well as an understanding of their experiences, then developed into problems that are proposed to obtain justification in the form of data. The population in this study were all students of the PTB Department. The population in this study were all parents of grade 2 students at SMK Negeri 3 Tondano from 5 majors (Computers and Networks, Electricity, Automotive, Building, Wood Creative Crafts). The test results show that there is a major problem, namely the role of parental motivation which is sufficient to encourage children to do something positive in their formal education. Motivation is a complex of forces, drives, needs, statements, tension-building or other mechanisms that become and become desirable activities for personal goals. What will be achieved, the clearer how the motivational action is carried out. Motivational actions will be successful if the goals are clear and realized by the motivated party and in accordance with the needs of the motivated parent. Keywords: The Role of Parents' Motivation and Continuation of Students' Study.